2011
DOI: 10.1007/s00464-011-1860-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial of simulator-based versus traditional in-surgery laparoscopic camera navigation training

Abstract: This is the first prospective randomized controlled study indicating that simulator-based training of camera navigation can be transferred to the OR using the traditional hands-on training as controls. In addition, simulator camera navigation training for laparoscopic surgery is as effective but more time efficient than traditional teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 33 publications
(45 reference statements)
1
36
1
Order By: Relevance
“…By the subjective GRS, the proficient group performed better on virtual (14 ± 6 [95% confidence interval {CI}, [10][11][12][13][14][15][16][17][18] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the subjective GRS, the proficient group performed better on virtual (14 ± 6 [95% confidence interval {CI}, [10][11][12][13][14][15][16][17][18] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been increased interest on the use of simulated models for evaluation of surgical proficiency. In a randomized controlled trial in general surgery, Franzeck et al [10] found that simulator-based training may be more efficient than intraoperative training. After experiencing similar on-screen practice times, the laparoscopic simulator group performed similarly to the intraoperatively trained group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will analyse concurrent validity [8] (comparison between the device and the old technique used for the same training purpose) and predictive validity [8] (whether or not the navigation skills acquired can improve trainee's performance in the operative room) as previously demonstrated by a few studies in relation to more complex and expensive systems [1,3,14,15]. In consideration of the references to clinical practice adopted in the development of the CHT (Table 1), the use of a two-arm prospective study could provide additional validity evidence to this training device.…”
Section: Discussionmentioning
confidence: 99%
“…For visualization of the operative field, surgeons rely daily on camera operators, who are usually the least experienced members of the team. Residents often use a laparoscopic camera for the first time in the operating room (OR) with no previous education or experience [1]. This can lead to sacrificing the additional benefits of an angled laparoscope for the simpler 0° alternative.…”
Section: Introductionmentioning
confidence: 99%